Influence of Intervertebral Level of Stenosis on Neurological Recovery and Reduction of Neck Pain After Posterior Decompression Surgery for Cervical Spondylotic Myelopathy: A Retrospective Multicenter Study with Propensity Scoring. Issue 6 (15th March 2022) - Nori, Satoshi; Nagoshi, Narihito; Aoyama, Ryoma; Ishihara, Shinichi; Fujiyoshi, Kanehiro; Shiono, Yuta; Kitamura, Kazuya; Ishikawa, Masayuki; Suzuki, Satoshi; Takahashi, Yohei; Tsuji, Osahiko; Yagi, Mitsuru; et al.
Abstract : Study Design: Retrospective multicenter study. Objective: To identify the impact of the intervertebral level of stenosis on surgical outcomes of posterior decompression for cervical spondylotic myelopathy (CSM). Summary of Background Data: As the upper affected cervical levels in elderly patients result from degenerative changes in the lower cervical levels with aging, it is usually difficult to determine the influence of the upper affected cervical levels on surgical outcomes after posterior decompression for CSM in older age. Methods: This study involved 636 patients with CSM who underwent posterior decompression. According to the most stenotic intervertebral level, patients were divided into upper (n = 343, the most stenotic intervertebral level was C2/3, C3/4, or C4/5) and lower (n = 293, the most stenotic intervertebral level was C5/6, C6/7, or C7/T1) cervical stenosis groups. Propensity score matching of the baseline factors (characteristics, comorbidities, and neurological function) was performed to compare surgical outcomes, the Japanese Orthopaedic Association (JOA) scores, and visual analog scale (VAS) for neck pain between the upper (n = 135) and lower (n = 135) cervical stenosis groups. Results: Before propensity score matching, age at surgery was older and pre- and postoperative JOA scores were lower in the upper cervical stenosis group ( P < 0.001, P < 0.001, and P < 0.001, respectively). Following matching, baseline factors were comparable between the groups. Postoperative JOA scores, preoperative-to-postoperative changes in the JOA scores, and the JOA score recovery rate were not significantly different between the groups ( P = 0.866, P = 0.825, and P = 0.753, respectively). No differences existed in postoperative VAS for neck pain and preoperative-to-postoperative changes in VAS for neck pain between the groups ( P = 0.092 and P = 0.242, respectively). Conclusion: The intervertebral level of stenosis did not affect surgical outcomes after posterior decompression for CSM. Level of Evidence: 3 Abstract : A retrospective multicenter study with propensity scoring revealed the impact of the intervertebral level of stenosis on surgical outcomes of posterior decompression for cervical spondylotic myelopathy. Functional recovery was not different between the upper and lower cervical stenosis groups. Posterior decompression is effective, regardless of the intervertebral level of stenosis.